x+15-4x-45=

Simple and best practice solution for x+15-4x-45= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+15-4x-45= equation:


Simplifying
x + 15 + -4x + -45 = 0

Reorder the terms:
15 + -45 + x + -4x = 0

Combine like terms: 15 + -45 = -30
-30 + x + -4x = 0

Combine like terms: x + -4x = -3x
-30 + -3x = 0

Solving
-30 + -3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '30' to each side of the equation.
-30 + 30 + -3x = 0 + 30

Combine like terms: -30 + 30 = 0
0 + -3x = 0 + 30
-3x = 0 + 30

Combine like terms: 0 + 30 = 30
-3x = 30

Divide each side by '-3'.
x = -10

Simplifying
x = -10

See similar equations:

| 5-a/2=7 | | 6n-54=-12n+36 | | 8x+5=t | | 3(9+5)=3*9+3*5 | | 4u+-7u=9 | | 12x+2=122 | | 35x^2-161x-70=0 | | 5-7n+4n=18-64 | | Y=-0.01X^2+0.6X+5.8 | | 16x^2-24x+6=0 | | 4n+20=53-2a | | h(t)=-16t^2+40t+9 | | 2(f+-7)=-10 | | -14=-18+n | | -10k=0 | | 59-13x=-139-7x | | -6x-5=4x+25 | | 87+(-96)= | | -4(x+2)=6x+10+12 | | -6x-5=4x+5 | | -3=3+v | | 13=6+(-r) | | 5+3*b=8-5*b | | 2x^2+19x+30=0 | | 2x*2+4x+4800=0 | | 6x+7-4x+5= | | 19n=-456 | | 486=27x | | 9(7y-3)-(7y+2)= | | -r-1=-10 | | -6-3k=-2k-(k+6) | | -101+4x=-7x+119 |

Equations solver categories